PENGARUH PROMOSI TERHADAP IMPULSE BUYING MELALUI POSITIVE EMOTION SEBAGAI VARIABEL MEDIASI DENGAN ETIKA KONSUMSI ISLAM SEBAGAI VARIABEL MODERASI PADA KONSUMEN MUSLIM SHOPEE - Aisyah Nawaratallah; Rianto Anugerah Wicaksono (Al-Iqtishad: Jurnal Ekonomi Syariah, 2024)
This study examines the effect of promotion on impulsive buying with positive emotion as a mediating variable and Islamic consumption ethics as a moderating variable, focusing on Muslim consumers in Shopee. Promotion, as an important element in marketing strategy, is expected to trigger impulsive buying through the positive emotion effect it creates. This study also explores how Islamic consumption ethics, which include principles such as fairness and sharia compliance, moderate the relationship between promotion and impulsive buying. Data were collected through an online survey involving Muslim consumers in Shopee, and analyzed using path analysis techniques to test the proposed hypotheses. The test results state that the promotion variable has a significant effect on positive emotion. The positive emotion variable has a significant effect on impulse buying. The promotion variable has a significant effect on impulse buying. The positive emotion variable on impulsive buying is not moderated by Islamic consumption ethics. In addition, Islamic consumption ethics is shown to moderate the effect of promotion on impulsive buying, with varying degrees ofmoderation depending on the extent to which consumers follow sharia principles in their shopping decisions. These findings provide important insights for marketing practitioners in designing promotional strategies that are effective and in line with Muslim consumer values, as well as contributing to the literature on consumer behavior in the context of Islamic marketing.